Adoecimento de policiais militares: Fatores de riscos psicossociais no trabalho e o processo de adoecimento de policiais militares no exercício da função. - REINALDO, Marcos da Silva (2024)
This study investigated and contextualized the relationship between illness, work, and psychosocial factors that contribute to the illness process of military police officers in the city of Imperatriz – MA. To this end, the research assessed psychosocial risks at work using the Work Orientation Scale (EOPT), the Managerial Styles Scale (EEG), the Psychosocial Stress at Work Scale (ESPT), and the Work Damage Scale (EDFPT). Based on the Psychodynamics of Work, it was considered that work can be a source of both pleasure and suffering. The study investigated psychosocial risks in two battalions of the PMMA, identifying factors of burnout, physical damage, and work organization issues. A total of 201 military police officers participated in the research, with 76.2% being male and 23.8% female. Data were collected through a sociodemographic questionnaire and semi-structured interviews on psychosocial risks related to work (PROART). The research was conducted in a descriptive and explanatory manner, with a quantitative and qualitative approach to the data analyzed. Results indicated a lack of personnel, low participation, lack of transparency in decisions, and deficient planning. The pressure for results harms the mental health and motivation of police officers. Poor working conditions and fragmented organization resulted in physical and mental damage, leading to occupational diseases. Officers adopt defensive strategies to protect their mental health, but interventions are necessary to promote a healthier work environment.